Adopting the GHOSHEH Model to Create Innovative Open Educational Resources Based on Rogers' Process for Diffusion of Innovations - Wahbeh, Dua' Ghosheh; Burgos, Daniel; Affouneh, Saida (Sustainability, 2023)
The current study aims to adopt a new model for creating innovative OERs. The model, called 'GHOSHEH', supports OERs through multiple learner-centered strategies with authentic assessments, and focuses on practice and reflection. The model is internally validated based on international experts' reviews. Rogers' process for diffusion of innovations is followed in order to introduce and adopt the GHOSHEH model based on a sample of 117 teachers and experts from different states in the Arab world, including Palestine, Jordan, Saudi Arabia, Oman, Kuwait, UAE, Iraq, and Yemen. Mixed methods research is used: qualitative data are collected from a descriptive case study, and quantitative data are collected from the responses of the participants to a questionnaire about adopting the GHOSHEH model. Results reveal that the model involves four main processes: The first is analysis of content and context. The second is implementing sequenced activities that promote reflection, problem solving, and collaboration. The third is a formative assessment followed by providing continuous feedback. The fourth is peer sharing of the created OERs. Moreover, results show that teachers and experts from different states in the Arab world overwhelmingly adopted the model, and there is evidence of the model's advantages, simplicity, compatibility, trialability, and observability.
Keywords: open educational resources (OERs); instructional design; models for creating innovations; GHOSHEH model; theory for diffusion of innovation (DOI); JCR